Analysis Of The Application Of Time Management In Building Projects With Critical Path Method (Cpm) And Earned Value Method (Evm) (Case Study: Jakarta Islamic Hospital Pondok Kopi) - Nabila Maulidanisa; Nikko Rozy (Departement of Civil Engineering, Universitas Winaya Mukti, 2026)
This study analyzes the implementation of time management in construction projects using the Critical Path Method (CPM) and Earned Value Method (EVM) methods in the construction project of the Jakarta Islamic Hospital Pondok Kopi. This research is motivated by the importance of time control in project implementation to minimize delays. The methods used include work network analysis using CPM to determine the critical path and duration of the project, as well as time performance analysis using EVM through the parameters of Planned Value (PV), Earned Value (EV), Schedule Variance (SV), and Schedule Performance Index (SPI). The results of the CPM analysis show that the duration of the project completion is 274 days, faster than the duration of the plan on the S curve which is 287 days. However, the results of the EVM analysis show that the project time performance is delayed, which is shown by the Schedule Performance Index (SPI) value of 0.77061 and the Schedule Variance (SV) value of negative. This indicates that the actual progress of the project is lower compared to the plan that has been set. Thus, although the project has the potential to be completed faster in terms of planning based on CPM analysis, the actual conditions on the ground indicate that the project is delayed. Therefore, more optimal control is needed, especially on critical path activities, to improve project time performance.